2010
DOI: 10.1016/j.cmet.2010.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Atherogenic Lipids and Lipoproteins Trigger CD36-TLR2-Dependent Apoptosis in Macrophages Undergoing Endoplasmic Reticulum Stress

Abstract: SUMMARY Macrophage apoptosis in advanced atheromata, a key process in plaque necrosis, involves the combination of ER stress with other pro-apoptotic stimuli. We show here that oxidized phospholipids, oxidized LDL, saturated fatty acids (SFAs), and lipoprotein(a) trigger apoptosis in ER-stressed macrophages through a mechanism requiring both CD36 and toll-like receptor 2 (TLR2). In vivo, macrophage apoptosis was induced in SFA-fed, ER-stressed wild-type but not Cd36−/− or Tlr2−/− mice. For atherosclerosis, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
332
1
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 411 publications
(352 citation statements)
references
References 75 publications
(117 reference statements)
11
332
1
8
Order By: Relevance
“…Intracellular calcium signaling regulates a wide range of cellular functions, including contraction, secretion, and metabolism. Whether the activation of calcium influx channels is important for CD36 function in phagocytosis, apoptosis (2,8), and thrombus formation (6, 69) is unknown and requires further study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intracellular calcium signaling regulates a wide range of cellular functions, including contraction, secretion, and metabolism. Whether the activation of calcium influx channels is important for CD36 function in phagocytosis, apoptosis (2,8), and thrombus formation (6, 69) is unknown and requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to facilitating lipid uptake, CD36 participates in the transduction of intracellular signaling events to activate stress kinases implicated in insulin resistance (7) and atherosclerosis (6). In ER-stressed macrophages, CD36 has been proposed to contribute to the suppression of ER survival pathways and the amplification of apoptotic cascades (2,8). Studies in humans have suggested the importance of CD36 function in both lipid uptake and inflammatory processes (9).…”
mentioning
confidence: 99%
“…On the other hand, the promotion of atherogenesis by an exogenous TLR2 ligand, Pam3CSK4, is suppressed by Tlr2 deficiency in the bone marrow 64) . In addition, while transplantation of Tlr2 −/− Tlr4 −/− bone marrow into lowdensity lipoprotein receptor knockout (Ldlr −/− ) mice does not affect the lesion area, it suppresses the necrotic area, with a reduced rate of macrophage apoptosis 65) . Moreover, bone marrow deficiencies in Trif and Tram, two adaptor molecules for TLR4 and TLR3, reduce the atherosclerotic lesion size 66) .…”
Section: Tlr Signaling In Atherosclerosismentioning
confidence: 99%
“…6,7 Among toll-like receptors, TLR2 and TLR4 are involved in the initiation and amplification of atherosclerosis. [8][9][10][11] Several studies substantiated that TLR2 and TLR4 were closely associated with vessel spots and artery stenosis degree in ACS patients. 12,13 Moreover, unlike TLR4 blockade, neutralizing TLR2 can inhibit the expression of NF-iB and the release of interleukin-6 (IL-6), IL-8, and matrix metalloproteinases.…”
Section: Introductionmentioning
confidence: 99%